1994
DOI: 10.1016/0014-5793(94)00718-7
|View full text |Cite
|
Sign up to set email alerts
|

The studies of cooperative regions in T7 RNA polymerase

Abstract: The heat denaturation of bacteriophage T7 RNA polymerase (T7RNAP) was studied by scanning microcalorimetry. The thermodynamic parameters of the denaturation were estimated within the pH range 6-9. The analysis of the denaturation curves showed the presence of two cooperative parts of the T7RNAP molecule melting according to the 'all-or-none' principle. The molecular masses of these parts were determined as 22 and 77 kDa. These values are close to the molecular masses of protein domains obtained from X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Two of them, S430P and N433T are located in the interface of NTD and CTD, S430P substitution enhances hydrophobic interaction with F268 and F416, thereby increase domain interaction (Figure 4B ). Scanning microcalorimetry measurement showed that the T m for CTD alone is 7°C lower than in the intact protein, strongly suggesting the CTD is stabilized by inter-domain interaction with the NTD ( 39 ). F880Y substitution generates hydrogen-bonding interactions with P474 and D879, thereby increasing internal stability of the CTD (Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Two of them, S430P and N433T are located in the interface of NTD and CTD, S430P substitution enhances hydrophobic interaction with F268 and F416, thereby increase domain interaction (Figure 4B ). Scanning microcalorimetry measurement showed that the T m for CTD alone is 7°C lower than in the intact protein, strongly suggesting the CTD is stabilized by inter-domain interaction with the NTD ( 39 ). F880Y substitution generates hydrogen-bonding interactions with P474 and D879, thereby increasing internal stability of the CTD (Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Facile cleavage of the protein into 20‐kD N‐terminal and 80‐kD C‐terminal fragments (Davanloo et al 1984; Tabor and Richardson 1985) suggests the presence of at least two domains. Previous calorimetric studies (Protasevich et al 1994) showed that unfolding of T7RNAP proceeds in two stages under the conditions they used, corresponding to disruption of two structural regions in the molecule.…”
mentioning
confidence: 99%